2020
DOI: 10.1016/j.mad.2020.111323
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of enhanced quiescence in neural stem cell aging

Abstract: The maintenance of neural stem cell function is vital to ensure neurogenesis throughout adulthood. During aging, there is a significant reduction in adult neurogenesis that correlates with a decline in cognitive function. Although recent studies have revealed novel extrinsic and intrinsic mechanisms that regulate the adult neural stem cell (NSC) pool and lineage progression, the precise molecular mechanisms that drive dysregulation of adult neurogenesis in the context of aging are only beginning to emerge. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 121 publications
(136 reference statements)
1
18
0
Order By: Relevance
“…Consistent with the known decrease in neurogenesis with age (Audesse & Webb, 2020;Corenblum et al, 2016;Daynac et al, 2016), we observed that NSPCs isolated from aged mice had a reduced proliferation rate compared to young (Figure S1A,B). To elucidate the age-associated chromatin changes in NSC quiescence and activation, we compared the young ATAC-seq and RNA-seq profiles to datasets collected in parallel from aged NSPCs isolated from 20-24 month-old mice.…”
Section: Quiescent Nspcs In the Aged Brain Exhibit Chromatin Accessibility Loss At Select Genes Involved In Metabolismsupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with the known decrease in neurogenesis with age (Audesse & Webb, 2020;Corenblum et al, 2016;Daynac et al, 2016), we observed that NSPCs isolated from aged mice had a reduced proliferation rate compared to young (Figure S1A,B). To elucidate the age-associated chromatin changes in NSC quiescence and activation, we compared the young ATAC-seq and RNA-seq profiles to datasets collected in parallel from aged NSPCs isolated from 20-24 month-old mice.…”
Section: Quiescent Nspcs In the Aged Brain Exhibit Chromatin Accessibility Loss At Select Genes Involved In Metabolismsupporting
confidence: 86%
“…NSC quiescence is a tightly regulated state characterized by a transcriptional program enriched for lipid metabolism, glycolysis, and specific cell signaling pathways. This transcriptional program is dramatically altered as NSCs activate, upregulating genes involved in oxidative metabolism, cell proliferation, and protein translation (Audesse & Webb, 2020;Llorens-Bobadilla et al, 2015;Morizur et al, 2018;Shin et al, 2015). Moreover, with NSC activation, aggregates of damaged proteins and molecular cargo that accumulate in qNSCs are cleared.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a highly integrated network of signals is required to maintain healthy lifelong neurogenesis and alterations to these signaling pathways during aging have been linked to the decline in neurogenesis (e.g., BMP, Notch, Wnt, EGF, and IGF). A number of age-associated intrinsic cellular changes impact neurogenesis in aged animals, including transcriptional, metabolic, proteostatic, and epigenetic changes (for an in depth review see Audesse and Webb, 2020 ). For example, a major age-associated feature of NSCs is the deterioration of protein quality control, including autophagy-lysosome function, chaperone activity, and overall aggregate processing.…”
Section: Main Textmentioning
confidence: 99%
“…For example, there was a strong enrichment for processes associated with neuronal fate commitment and differentiation, such as axon guidance, synapse maturation, and neuronal migration ( Figures 1A and S1B ). Moreover, features of the quiescent state such as high fatty acid beta-oxidation, autophagic flux, cell cycle restraint, and transcriptional repression 70 were upregulated in the FOXO3 high tumor samples ( Figure 1A and S1C ). Overall, FOXO3 high tumors tended to have elevated FOXO3 protein levels as well ( Figure S1D ), further supporting distinct quiescence-like hallmarks of FOXO3 high GBMs.…”
Section: Resultsmentioning
confidence: 99%